Hypertension: Diagnosis and management in primary care. Issue 9 (September 2021) - Afroze, Ayesha; Mohammed, Imran
The global prevalence of hypertension is high and continues to rise, making it an increasingly common condition managed in primary care. Untreated hypertension can cause end-organ damage leading to complications that increase morbidity and mortality from cardiac, renal, and cerebrovascular disease. Hypertension can significantly affect an individual patient's quality of life and can cause a considerable strain on the healthcare system. If hypertension is detected early, these events are avoidable, as there is an opportunity for intervention at a much lesser cost. Several proven, highly effective, and well-tolerated lifestyle and drug treatment strategies can achieve reduction in blood pressure. The aim of this article is to illustrate evidence-based steps that are applicable in the diagnosis and management of hypertension in primary care.